Semi-Fixed Space Maintainer Treatment In Premature Loss Deciduous Tooth - Nabila Clara; Jeffrey . (Maranatha Christian University, 2020)
Introduction: The period of deciduous teeth is an important period in child development. Damage to deciduous teeth that occur and cannot be treated conservatively will cause premature decay of teeth which is often called premature loss. A space maintainer is a passive tool used to maintain dental arches due to premature loss of deciduous teeth. Method: An 11-year-old girl accompanied by her mother came to RSGMP Unjani in 2018 with complaints of lower right back teeth missing because they have removed. The patient's mother is worried that her replacement teeth will not grow properly. Intraoral examination revealed tooth loss 85. The study model was analyzed using the Moyers method. Results: Analysis of the lower jaw model showed excess space. Patients were treated with a semi-fixed band and loop space maintainer on teeth 85. Conclusion: Premature loss results in excess space in the arch, so as to prevent further occlusion abnormalities in the child's growth and development process, we need a special tool used to maintain space due to premature loss of deciduous teeth.